Pemanfaatan Tandan Kosong Kelapa Sawit dan Pupuk Nitrogen Sebagai Substitusi Top Soil terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq.) PeriodePre Nursery - SITIO, YOSEPH; WIJANA, GEDE; RAKA, I GUSTI NGURAH (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.4, No.4, Oktober 2015, 2016)
ABSTRACT The Utilization of Oil Palm Empty Bunches and Nitrogen Fertilizer as Substitution of Top Soil on Growth of Oil Palm Seedling ( Elaeis guineensis Jacq.) in Pre Nursery Palm oil ( Elaeis guineensis Jacq.) is the leading commodity in Indonesia, Indonesia can produce 23.900 ton or 40,27% of the total world production palm oil. To increase the production of palm oil so it’s necessary to the expansion of oil palm plantations. Media used for oil palm seedling is top soil, difficulty to get top soil it’s because it’s used continuously or eroded due to erosion so the availability of top soil is limited. Therefore, needed alternative to substitusion of top soil as a media of oil palm seedling. The purpose of this research was to know potential of compost oil palm empty bunches (TTKS) and nitrogen fertilizer as substitution of top soil on growth of oil palm seedling in pre nursery. This research used randomized complete block design with 2 factors. The first factors is media with top soil + sub soil + sand (3:1:1), TKKS compost + sub soil + sand 3:1:1, 1:3:1, 2:2:1, 2:1:2, 1:2:2 and the second factors is doses nitrogen fertilizer (urea 46%) with 0 g urea/pot, 2 g urea/pot and 4 gurea/pot.The research result showed that media TKKS compost + sub soil + sand 2:2:1 and 3:1:1 can substitution top soil because it has a value that is greater than or equal to the observed variable with controls. The application of nitrogen 4 gurea/seed showed the maximal growth of oil palm seedling in pre nursery.  The interaction of the both treatment just significant to plant height 4 and 12 weeks after planting, leaf area 4 weeks, steam diameter and leaf  number 8 weeks,  fresh weight of  crown 12 we eks. Composition of TKKS compost + sub soil + sand 3:1:1 + 4 g urea/pot is the best composition as a substitution of top soil because the value of  parameters plant height, leaf number, total chorophyll, fresh weight of crown, fresh weight total and dry weight total are greater than or equal to top soil. Keyword : TKKS compost and Nitrogen, substitution top soil, pre nursery